Early Diagnosis of Wilson’s Disease in Children in Southern China by Using Common Parameters - Zhou, Jianli; Zhang, Qiao; Zhao, Yuzhen; Chen, Moxian; Zhou, Shaoming; Cheng, Yongwei (Frontiers in Genetics, 2022)
Objective: The aim of the study was to develop the early diagnostic criteria for Wilson’s disease (WD) in young children in southern China by using alanine aminotransferase (ALT) elevation as the first manifestation. Methods: A cross-sectional retrospective analysis of the clinical data and genetic test results of children with WD in southern China in the past 4 years and the follow-up of their short-term prognosis were performed in this study. Results: A total of 30 children (5.08 ± 2.06 years old) with elevated ALT as the first manifestation of WD in southern China were enrolled in this study, including 14 females and 16 males. Specifically, in all of the 30 cases (100%), the serum ceruloplasmin (CP) level was decreased, whereas the 24-h urinary copper level was increased. The genetic mutation test of the ATP7B gene was used to confirm the diagnosis. In particular, the two mutation sites, including p.R778L and p.I1148T, had the highest mutation frequencies, approximately 23.0 and 10.7%, respectively. Through follow-up, most of the children had good recovery. Conclusion: Early diagnosis and treatment of WD would substantially increase the survival rate and have a better prognosis. In addition, in 5-year-old children from southern China, early diagnosis could be performed quickly by referring to the following three parameters: elevated ALT, decreased ceruloplasmin level, and increased 24-h urinary copper level. It lays a foundation for further studies with a larger sample size.